O grande mentecapto, de F. Sabino : a construção literária e social do anti-herói Geraldo Viramundo - Aragão, Hudson Oliveira Fontes (2015)
We will analyse O grande mentecapto: relato das aventuras e desventuras de Viramundo e de suas inenarráveis peregrinações (1979), the second novel of the “mineiro” writer Fernando Sabino. We considered the work as neopicaresque, such as the theoretical approach of González (1994), and we had in mind that it is a comical genre of literature as well and to apply for a popular setting of main character: the roguery, in the Brazilian literature, usually is followed by the chimerical idealism of Don Quijote (1605; 1615), by Miguel de Cervantes Saavedra. Far beyond of the comical and quixotic adventures, the anti-hero of the novel reverberate as well the tragic face of his intertextual model, because Geraldo Viramundo, “mineiro” walker, will be arrested, interned in psychiatric asylums and including murdered by the crowd, in a public lynching, being a scapegoat, just like Jesus Christ. The violence that the main character is submitted in the plot will be analysed, second the modern jurisprudence, through Michel Foucault (1975), and in an anthropologic and religious level, via René Girard (1972; 1975). The way of analysis will consider still the Brazilian representations – specially the Tiradentes – and the universal ones of the novel (more precisely the Christian elaboration of the main character) and the study will conclude that, in a national point of view, O grande mentecapto is pessimistic, but from the human and universal point of view, it propitiate us, in the chimerical space of the future, a possible escape of the violences that operates the mechanisms of the social coercion.